2015
DOI: 10.1186/s12879-015-0763-9
|View full text |Cite
|
Sign up to set email alerts
|

Human brucellosis occurrences in inner mongolia, China: a spatio-temporal distribution and ecological niche modeling approach

Abstract: BackgroundBrucellosis is a common zoonotic disease and remains a major burden in both human and domesticated animal populations worldwide. Few geographic studies of human Brucellosis have been conducted, especially in China. Inner Mongolia of China is considered an appropriate area for the study of human Brucellosis due to its provision of a suitable environment for animals most responsible for human Brucellosis outbreaks.MethodsThe aggregated numbers of human Brucellosis cases from 1951 to 2005 at the municip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 54 publications
(75 reference statements)
3
48
0
1
Order By: Relevance
“…This trend is consistent with the profile of the whole nation [21, 22, 24, 31] and other northern provinces, such as the Inner Mongolia Autonomous Area [25] and Shandong Province [27]. Sero-prevalence studies have also indicated an increasing drift in both livestock (0.7% in 2005–2006, and 1.5% in sheep in 2009, 3.71% in 2014) and occupational population (13.3% in 2005–2006, 22.0% in 2007, and 22.8% in 2011) [18–20, 44].…”
Section: Discussionsupporting
confidence: 87%
“…This trend is consistent with the profile of the whole nation [21, 22, 24, 31] and other northern provinces, such as the Inner Mongolia Autonomous Area [25] and Shandong Province [27]. Sero-prevalence studies have also indicated an increasing drift in both livestock (0.7% in 2005–2006, and 1.5% in sheep in 2009, 3.71% in 2014) and occupational population (13.3% in 2005–2006, 22.0% in 2007, and 22.8% in 2011) [18–20, 44].…”
Section: Discussionsupporting
confidence: 87%
“…Jia at al. [15] conducted spatial statistical analysis to study the epidemiology of human brucellosis in Inner Mongolia.…”
Section: A Rt I C L E I N F Omentioning
confidence: 99%
“…Hoy en día, a más de 100 años de que Zammit asociara a Brucella con la leche de cabra, la fiebre de Malta sigue causando enfermedad tanto en animales como en el hombre en varias regiones del planeta. Sin embargo, países como Canadá, E.U.A., Japón, el norte y centro de Europa, Australia y Nueva Zelandia han logrado erradicar esta enfermedad 8,9 . 15 .…”
Section: David Bruce Y Brucellaunclassified